Management Control Systems in the Digital Age: Concepts, Implementation, and Implications - Rodiah Aprilia; Dilla Ayu Kartika; Yuliana Dewi Siregar; Jufri Darma (Universitas Mohammad Husni Thamrin, 2025)
Management Control Systems (MSS) play a central role in ensuring organizational goals are achieved and are undergoing significant changes driven by digital technology. The use of big data analytics, artificial intelligence, and enterprise resource planning makes control processes faster, more accurate, and more real-time. This study aims to explain the concept of MSS in the digital era, examine its application in Indonesian organizations, and discuss the managerial and governance implications and emerging challenges. Since its introduction, MSS has served as a critical tool for managers to direct, monitor, and evaluate operational activities and corporate strategy. The research was conducted through a literature review combining narrative and systematic reviews based on the PRISMA framework, using accredited literature sources from 2020 to 2025. The study results indicate that digital MSS is no longer merely an administrative tool but has become a strategic instrument that helps organizations respond more adaptively to business complexity. However, cybersecurity risks, complex system integration, and internal cultural resistance remain key obstacles. Successful implementation is largely determined by the harmony between technology, human resource competency, a supportive organizational culture, and clear regulations. The contribution of this study lies in mapping the latest literature and providing practical recommendations for designing SPM that is adaptive, accountable, and in line with the dynamics of business digitalization.